Advanced information systems engineering : 31st international conference, CAiSE 2019, Rome, Italy, June 3-7, 2019, Proceedings /: 31st international conference, CAiSE 2019, Rome, Italy, June 3-7, 2019, Proceedings. ([2019]) - Unknown
No abstract available